Socio-Economic Value Chain Dynamics of Banana Chips Micro-Enterprise: A Case Study of UD Dwi Tunggal in Lumajang, Indonesia - Ninda Parwana, Risa (Journal of Supply Chain and Entrepreneurship, 2025)
Background: Banana chips micro-enterprises play a significant socio-economic role in rural Indonesia, particularly in regions where agriculture and household-scale processing form the foundation of local livelihoods. UD Dwi Tunggal in Lumajang represents a long-standing community-based enterprise whose production system, value distribution, and inter-actor relationships have not yet been examined through a socio-economic value chain perspective. Understanding these dynamics is essential to reveal how small enterprises sustain competitiveness amid growing market pressures and shifting consumer preferences. Aims: This study aims to investigate the socio-economic dynamics of the banana chips value chain at UD Dwi Tunggal, with a focus on identifying key actors, mapping value creation processes, and analyzing how financial and non-financial benefits are distributed across the chain. Methods: A descriptive qualitative–quantitative design was employed, combining field observations, semi-structured interviews, and cost–value computations. Primary data were collected from banana suppliers, enterprise owners, and regional distributors. Value chain mapping followed Porter’s activity framework, while added value was calculated using a modified Hayami method to quantify income distribution and labor contributions. Results: The findings show that the value chain is driven by three main actors—suppliers, processors, and distributors—whose interactions shape production continuity and market access. Monthly production costs reached approximately IDR 19.8 million, while revenue averaged IDR 54 million. The added value generated was IDR 71,464 per kilogram, indicating strong conversion efficiency and high economic contribution at the processing level. Socially, the enterprise functions as a stable livelihood source for workers and strengthens local supply networks. Conclusion: The study concludes that UD Dwi Tunggal’s value chain demonstrates both economic resilience and socio-cultural embeddedness, enabling the enterprise to sustain competitiveness through localized supplier relationships, community-based labor structures, and consistent product demand. These findings highlight the importance of strengthening rural micro-enterprises as socio-economic anchors in regional development.